AN ANALYTICAL STUDY OF INVESTMENT MANAGERS' PERCEPTION TOWARDS QUALITY DIMENSIONS OF CREDIT RATING SERVICE (International Journal of Food and Nutritional Sciences, 2022)
This study aims to analyze the level of satisfaction of investment managers regarding credit rating services by various rating agencies. Data were collected from 120 investment managers of Delhi-NCR using a semi-structured questionnaire. Their opinions about Credit Rating services were measured using a five-point Likert scale. The exploratory Factor Analysis technique was applied, and all the statements were loaded into two factors: effectiveness of Credit Rating and Assessment Quality of Credit Rating Agencies. Factors affecting the satisfaction of investment managers with these two dimensions were identified by applying discriminant analysis technique using IBM SPSS 26. The findings of the study highlighted that the volume of investment and the general investment horizon play the most significant role in discriminating the satisfaction level of investment managers. Although a majority of investment managers involved in long-term investment practices are highly satisfied with the credit rating service, the managers with a long experience in the field and making huge investments for the short term are comparatively less satisfied with credit rating. As experienced investors in the field are less satisfied with the credibility of ratings, these are the post-rating facilities such as rating surveillance, rating review, and rating outlooks services that lack their intended quality. Therefore the rating agencies should work on short-term creditworthiness analysis and their post-rating appraisal procedures.